Changes in the Effect of Capital and TFP on Output in Penn World Tables 7 and 8: Improvement or Error? (2015)
Lower ICP 2005 construction prices in developing countries increase the effect of capital on output in PWT 7.1 and 8.0 and cause negative world TFP growth during 1990-2010 in PWT 8.0. The investment data appear to be more accurate in PWT 6.3.